Integrating Blockchain with Edge AI for Secure Data Sharing in Decentralized Cloud Systems - Manduva, Vinay Chowdary (International Journal of Scientific Research and Management (IJSRM), 2024)
Blockchain integrated with edge AI has a new concept that can transform secure data sharing in decentralized cloud networks. This paper looks at how these two emerging technologies can be integrated to solve some of the most important issues facing today’s technology society including data privacy, security, and system scalability specifically scenarios with decentralized systems. Blockchain offers a secure and decentralized environment for the exchange of data and smart contracts, and edge AI improves system performance and minimizes data transfer time by analyzing data at the source. Together, they allow desirable qualities in and reliable structures for Applications in healthcare, IoT, SCM and FinTech.This paper defines and describes the rationale, fundamentals, and advantages of blockchain, edge AI, and decentralized cloud systems. It suggests the approach to combine these technologies and outlines main advantages, such as increasing the security level, opportunity to provide real-time data analysis, and cost-savings. Also, the paper demonstrates real-world application of federated learning in healthcare and in the context of blockchain IoT application areas, lingering the possibilities of revolutionary advancements.However, there are spheres such as resource constrains, scaling issues, and integration barriers that needs to be further discussed in order to commercialize the technology extensively. Discussing future prospects, the paper reveals lightweight blockchain solutions, artificial intelligence-based consensus algorithms, and the need for collective work on the decentralized architecture of large numbers of users. This integration is a milestone on the road to building a Safe, Secure, Intelligent Integrated Decentralized system, the new paradigm to share and process the information between industries.